Promoting Ekowisata-Agroforestry Berbasis Digital untuk Meningkatkan Sosio-Ekonomi Masyarakat di Desa Batu Putih Sekotong Lombok Barat - Zaini, Muh; utama, Lalu Wahyu putra; muhamad supriadi (Bhinneka Publishing, 2022)
Batu Putih Village is one of several villages in West Sekotong. Geographically, this area is in a strategic location enriched with coastal areas and a series of hills. Like other areas in Sekotong, which are developing tourism potential based on the potential of existing villages, Batu Putih village is also developing as a tourist village by developing a tourism concept by designing a village with herbal plants. One of the concrete steps taken in optimizing the potential as well as accelerating the introduction of Batu Putih village into the wider community is a platform for promoting tourism that is being promoted by the local community. The service carried out by the Nurul Hakim Islamic Institute focuses on efforts to promote Batu Putih village and its efforts to improve the socio-economic community. Therefore, this research is entitled